2009
DOI: 10.1002/mop.24231
|View full text |Cite
|
Sign up to set email alerts
|

Design and development of a broadband amplitude compensated long time delay circuit on thin‐film liquid crystal polymer

Abstract: and the effect of the finite ground which has not been included in the simulation procedure. The passband insertion loss is about 2.4 dB, which is mainly due to the conductor and dielectric losses of the substrate. The 3-dB bandwidth is 5.3%. Two transmission zeros at 0.97 GHz and 1.04 GHz are observed as expected. The out-of-band rejection is better than 31.5 dB at the lower stopband and 29 dB at the upper stopband. CONCLUSIONIn this article, a novel compact slow-wave open-loop resonator has been presented to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Ta et al reported a compact broadband balun in 2013 [65] (see Figure 4e) and Pham et al reported a UWB low-loss balun with stacked-defected grounding in 2018 [67], both of which are preferable for antenna design. A long-time-delay circuit with a broad bandwidth was reported in [68], whose 2-bit relative delay reached up to 600 ps. Chieh and Pham developed a flexible Wilkinson power divider with integrated thin-film resistors, achieving a wide bandwidth ratio of 9:1 within a compact size [69].…”
Section: Other Circuit Componentsmentioning
confidence: 99%
“…Ta et al reported a compact broadband balun in 2013 [65] (see Figure 4e) and Pham et al reported a UWB low-loss balun with stacked-defected grounding in 2018 [67], both of which are preferable for antenna design. A long-time-delay circuit with a broad bandwidth was reported in [68], whose 2-bit relative delay reached up to 600 ps. Chieh and Pham developed a flexible Wilkinson power divider with integrated thin-film resistors, achieving a wide bandwidth ratio of 9:1 within a compact size [69].…”
Section: Other Circuit Componentsmentioning
confidence: 99%